2020
DOI: 10.1002/cne.24923
|View full text |Cite
|
Sign up to set email alerts
|

Differences in behavior between surface and cave Astyanax mexicanus may be mediated by changes in catecholamine signaling

Abstract: Astyanax mexicanus is a teleost fish that is in the process of allopatric speciation. Ancestral Astyanax are found in surface rivers and derived blind forms are found in cave systems. Adaptation to life in nutrient poor caves without predation includes the evolution of enhanced food seeking behaviors and loss of defensive responses. These behavioral adaptations may be mediated by changes in catecholaminergic control systems in the brain. We examined the distribution of tyrosine hydroxylase, a conserved precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
(89 reference statements)
0
0
0
Order By: Relevance
“…In A. mexicanus, evidence supporting this has been found for several traits and genes behind them. For example, due to the shared pool of the Ltyrosine precursor loss-of-function mutations in oca2 gene responsible for complete pigment loss (i.e., albino phenotype) also affect catecholamine synthesis which in turn affects several physiological and behavioral traits (Bilandžija et al, 2013(Bilandžija et al, , 2018Gallman et al, 2020;O'Gorman et al, 2021). Recently, a genome wide analysis of A. mexicanus found that losses of traits like pigment and eyes show signatures of positive selection which again speaks for the pleiotropic function of associated genes (Moran et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In A. mexicanus, evidence supporting this has been found for several traits and genes behind them. For example, due to the shared pool of the Ltyrosine precursor loss-of-function mutations in oca2 gene responsible for complete pigment loss (i.e., albino phenotype) also affect catecholamine synthesis which in turn affects several physiological and behavioral traits (Bilandžija et al, 2013(Bilandžija et al, , 2018Gallman et al, 2020;O'Gorman et al, 2021). Recently, a genome wide analysis of A. mexicanus found that losses of traits like pigment and eyes show signatures of positive selection which again speaks for the pleiotropic function of associated genes (Moran et al, 2023).…”
Section: Discussionmentioning
confidence: 99%